Ground Penetration Radar in Geotechnics. Advantages and Limitations - Quinta-Ferreira, Mário (2019)
The use of the Ground Penetration Radar (GPR) in geotechnics presents great potential, but also relevant difficulties. This technique allows the acquisition of field data in a fast and versatile way, facilitating the interconnection between the geological studies, the geophysical characterization, the mechanical exploration and the geotechnical zoning. The depth and accuracy of data acquisition easily adapts to various situations ranging from a few centimetres to several tens of meters, changing to antennas with lower frequency. This near surface and non-destructive test method can be used almost anywhere. The continuity of the information obtained with the GPR complements the discreet and localized information obtained with the mechanical exploration. The validation of the local geological conditions using direct mechanical exploration together with the GPR imaging allows the confirmation of the parameters obtained by techniques of different nature, that once validated can allow the interpretation of areas and volumes with improved accuracy. In favourable conditions the use of the GPR can greatly help the direct mechanical exploration but the interpretation must always be done with great care and based on a good knowledge of the site characteristics. The interpretation of the GPR has in most cases many uncertainties. The research developed aimed at increasing the geotechnical characterization efficiency, using complementary techniques in order to reduce the costs and the time required to perform the geotechnical studies, ensuring that the information obtained is suitable and sufficient for the intended purposes. In a few case studies the GPR was used conjugated with trenches and the Dynamic Probing Super Heavy (DPSH) test, and allowed to enhance the individual information of each technique, increasing reliability, taking into account the importance of the geology of each site. In the geotechnical study for the rehabilitation of an ancient Villa, requiring the construction of a small auditorium in the basement and an underground garage in the garden, the GPR and the DPSH successfully allowed to define the geotechnical zoning of the surface soils and of the depth of the sandstone bedrock, as the local information obtained by the DPSH allowed to validate the GPR imaging. The presence of buried pipes and of an underground water tank were also identified by a GPR grid. In karst areas the interpretation of the GPR can be complex due to the irregular geological interface between the limestone and the residual soils filling the dissolution zones. In aeolian sands the layers structure and the change in grain size are usually well identified with the GPR imaging, which can be validated by the geological reconnaissance and the mechanical exploration. Besides the natural variation of the electromagnetic properties of the ground mass, unexpected causes like tree roots, uncontrolled fill or even previous excavations can difficult a clear interpretation of the GPR data.